Urinary podocyte markers in diabetic kidney disease - Chuanlei Li; Cheuk-Chun Szeto (The Korean Society of Nephrology, 2024)
Podocytes are involved in maintaining kidney function and are a major focus of research on diabetic kidney disease (DKD). Urinary biomarkers derived from podocyte fragments and molecules have been proposed for the diagnosis and monitoring of DKD. Various methods have been used to detect intact podocytes and podocyte-derived microvesicles in urine, including centrifugation, visualization, and molecular quantification. Quantification of podocyte-specific protein targets and messenger RNA levels can be performed by Western blotting or enzyme-linked immunosorbent assay and quantitative polymerase chain reaction, respectively. At present, many of these techniques are expensive and labor-intensive, all limiting their widespread use in routine clinical tests. While the potential of urinary podocyte markers for monitoring and risk stratification of DKD has been explored, systematic studies and external validation are lacking in the current literature. Standardization and automation of laboratory methods should be a priority for future research, and the added value of these methods to routine clinical tests should be defined.